IDNLearn.com is the perfect place to get answers, share knowledge, and learn new things. Find the answers you need quickly and accurately with help from our knowledgeable and dedicated community members.
Sagot :
I am assuming that (3x4) = 12. Therefore,
12 * (3x-4) = 36x-48 ANS.
(3x-4)(3x-4) ???
You have to times each of the numbers from the opposite brackets together :)
3x x 3x = 9x^2
3x x -4 = -12x
-4 x 3x = -12x
-4 x -4 = 16 (a minus times a minus is a plus)
So it's 9x^2 -12x -12x +16
Which can be simplified to...
9x^2 -24x +16
;D
You have to times each of the numbers from the opposite brackets together :)
3x x 3x = 9x^2
3x x -4 = -12x
-4 x 3x = -12x
-4 x -4 = 16 (a minus times a minus is a plus)
So it's 9x^2 -12x -12x +16
Which can be simplified to...
9x^2 -24x +16
;D
We appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. Thanks for visiting IDNLearn.com. We’re dedicated to providing clear answers, so visit us again for more helpful information.